Intergenerational mobility shapes socio-economic inequities in mortality: Evidence from linked Dutch registers - Thompson, Kristina; Wiertsema, Sara (International Journal of Population Data Science, 2026)
Socioeconomic status (SES) strongly predicts survival in the Netherlands: those in the top 10% of the income distribution live about eight years longer than those in the bottom 10%. Evidence suggests these inequalities have widened over the twentieth century, although the underlying mechanisms remain unclear. One proposed explanation is that rising intergenerational mobility has altered the composition of socioeconomic groups, concentrating characteristics associated with poor health within groups with low SES. This study provides one of the first empirical tests of this hypothesis. We examine whether intergenerational social mobility influences age and cause of death in the Netherlands, by linking historical and contemporary population registers. Ancestors are identified in the Historical Sample of the Netherlands (observed 1883–2010), and descendants are identified in the System of Social-Statistical Datasets (observed 1994–2024). Our analytical sample includes 60,369 individuals from 37,495 families who survived to at least age 40 and are linked to at least one ancestor. We use Cox proportional hazards models for all-cause mortality and competing risks models for cause-specific mortality. Key predictors are ancestors’ occupational status and a categorical measure of descendants’ social mobility. Preliminary results show that the proportion of individuals with high SES in both childhood and adulthood increased across cohorts. These individuals experienced the lowest mortality risk. Those who remained low SES had the highest risk, despite declining in number. Upwardly mobile individuals experienced intermediate risks. Overall, mortality inequities widened over time, suggesting intergenerational mobility contributes to the growing social gradient in survival.